THE ORIGIN, CLINICAL COURSE AND SPECIFICITY OF TREATMENT OF ACUTE MIDDLE OTITIS - Akramov A. S.; Norboev Z. K. (Scholars Digest Publishing, 2024)
In the treatment of patients with acute purulent otitis media, at present, three main directions can be distinguished: conservative with the help of various drugs; surgical, including micro-surgical interventions; physiotherapeutic. In recent years, many complex treatments for acute purulent otitis have been developed. However, this problem has led otorhinolaryngologists to the need to revise traditional conservative methods due to their inefficiency and search for new treatments. One of these methods is to apply different types of physical energy: magnetic, laser, electromagnetic, etc.among them, the most effective is laser therapy (LT), which is widely used in inflammatory diseases of the QTB organs. The appointment of rational antibiotic therapy (rabt) is a very urgent problem, the solution of which depends on a number of factors of undoubted interest for practice.
Keywords: low intensity laser radiation, acute purulent otitis media, acute otitis media, ear, throat, nasal organs, antibiotic therapy.